2018
DOI: 10.4274/balkanmedj.2018.0477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single and Prolonged Fluoroquinolone Prophylaxis and Risk Factors for Infectious Complications After Transrectal Prostate Biopsy

Abstract: Background:The ideal prophylaxis duration for transrectal ultrasonography-guided prostate biopsy is incompletely defined.Aims:To compare the infectious complications of transrectal ultrasonography-guided prostate biopsy with and without extended antibiotic prophylaxis. The secondary aim was to evaluate the risk factors for infectious complications.Study Design:Prospective observational study.Methods:Four hundred patients who underwent transrectal ultrasonography-guided prostate biopsy were recruited. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As recommended by the clinical practice guidelines in surgery, we routinely administer prophylactic preoperative antibiotics in all craniotomies [10]. While routine administration of postoperative antibiotics is common practice in many institutions, the risk of surgical site infection (SSI) remains unaffected [6,22,24,27,46].…”
Section: Effect Of Prophylactic Antibiotics On Clinical Coursementioning
confidence: 99%
“…As recommended by the clinical practice guidelines in surgery, we routinely administer prophylactic preoperative antibiotics in all craniotomies [10]. While routine administration of postoperative antibiotics is common practice in many institutions, the risk of surgical site infection (SSI) remains unaffected [6,22,24,27,46].…”
Section: Effect Of Prophylactic Antibiotics On Clinical Coursementioning
confidence: 99%
“… 28 30 Unfortunately, in recent years, studies have found that the pathogenic bacteria Escherichia coli after TURS-PB resistance to quinolone antibiotics is as high as 80–90%. 29 , 31 , 32 In this study, we found that SIRS pathogens after TRUS-Bx showed strong resistance to levofloxacin, ciprofloxacin, gentamycin, penicillin G, compound Xinnuoming and the second-generation cephalosporins, with a resistance rate of 42.86%–80.95%. Therefore, we suggest that the preventive use of levofloxacin may need to be adjusted.…”
Section: Discussionmentioning
confidence: 71%
“…A nationwide study in Taiwan involving 12,968 TRUS‐bx procedures found that 6.59% of patients had infection complications and demonstrated that age, prostate cancer and hospitalisation were significant risk factors for severe infection 15 . Another study demonstrated that previous antibiotic usage within 3 months increased UTI development fater TRUS‐bx 23 . Elsewhere, a 10‐year case‐control investigation showed that infectious complications rose in the study period, and that recent hospitalisation, diabetes and chronic pulmonary obstructive disease from smoking were significant risk factors for infection 5 .…”
Section: Discussionmentioning
confidence: 99%
“…15 Another study demonstrated that previous antibiotic usage within 3 months increased UTI development fater TRUS-bx. 23 Elsewhere, a 10-year case-control investigation showed that infectious complications rose in the study period, and that recent hospitalisation, diabetes and chronic pulmonary obstructive disease from smoking were significant risk factors for infection. 5 Similarly, our study demonstrates that age, diabetes and prostate cancer are significantly higher in patients with postbiopsy UTI and the involvement of both diabetes and age are independent risk factors for biopsy-related infections of this kind.…”
Section: Discussionmentioning
confidence: 99%